2008
DOI: 10.1017/s0022215107001648
|View full text |Cite
|
Sign up to set email alerts
|

A maternal hereditary deafness pedigree of the A1555G mitochondrial mutation, causing aminoglycoside ototoxicity predisposition

Abstract: We confirmed that the A1555G mutation is a 'hot spot' associated with non-syndromic, inherited hearing loss. This mutation may play a vital role in the pathogenesis of hearing impairment, and can result in various grades of deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…These mitochondrial variants produce variable clinical severity with age of onset ranging from congenital to adulthood (Guan, ). Pathogenic alleles in the MT‐RNR1 gene can cause maternally inherited, nonsyndromic hearing loss which is induced or aggravated by ototoxic aminoglycosides such as gentamicin, kanamycin and streptomycin (Fischel‐Ghodsian et al., ; Gardner et al., ; Usami et al., ; Estivill et al., ; Li et al., ; Bai et al., ; Lu et al., 2010). However, in the absence of aminoglycoside antibiotics, the variants in the MT‐RNR1 gene produce the same phenotypes (Prezant et al., ; Shoffner et al., ; Bacino et al., ; Matthijs et al., ; Pandya et al., ; Estivill et al., ; Matsunaga et al., ; Liu et al., ; Zhu et al., ; Shen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These mitochondrial variants produce variable clinical severity with age of onset ranging from congenital to adulthood (Guan, ). Pathogenic alleles in the MT‐RNR1 gene can cause maternally inherited, nonsyndromic hearing loss which is induced or aggravated by ototoxic aminoglycosides such as gentamicin, kanamycin and streptomycin (Fischel‐Ghodsian et al., ; Gardner et al., ; Usami et al., ; Estivill et al., ; Li et al., ; Bai et al., ; Lu et al., 2010). However, in the absence of aminoglycoside antibiotics, the variants in the MT‐RNR1 gene produce the same phenotypes (Prezant et al., ; Shoffner et al., ; Bacino et al., ; Matthijs et al., ; Pandya et al., ; Estivill et al., ; Matsunaga et al., ; Liu et al., ; Zhu et al., ; Shen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mutation m.1555A>G has been associated with aminoglycoside-induced and nonsyndromic hearing loss. Different familial studies revealed that the m.1555A>G mutation carriers are susceptible to hearing loss after treatment with aminoglycosides even at low doses (Gardner et al, 1997;Fischel-Ghodsian et al, 1997;Usami et al, 1997;Estivill et al, 1998;Bai et al 2008). However, in the absence of aminoglycoside exposure the same mutation produces a clinical phenotype that varies considerably among family members and ranges from (i) severe congenital hearing loss, (ii) to moderate progressive hearing loss of later onset, (iii) to completely normal hearing (Prezant et al, 1993;Shoffner et al, 1994;Matthijs et al, 1996;Pandya et al, 1997;Estivill et al, 1998;Matsunaga et al, 2005;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Forty-two articles[ 3 6 7 9 10 11 12 13 16 17 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ] (the others are as shown in Figure 2 ) addressed the prevalence/incidence of MT-RNR1 mutation in the populations with SNHL for which a range of 0% in Brazilian[ 30 ] and Argentine[ 32 ] subjects to 100% in 3 Spanish families[ 31 ] with aminoglycoside-induced hearing loss were presented. The modal prevalence was 3.2% and only A1555G and/or C1494T variants were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Three papers documented ototoxicity in patients with no observed MT-RNR1 mutations[ 9 21 24 ] while two papers had no hearing impairment among patients with the mutation with or without the gentamicin exposure. [ 26 33 ] Eight papers[ 7 17 22 26 29 35 36 37 ] recorded a wide phenotypic variance of hearing impairment, age-of-onset and audiometric configurations in patients with the mutation and hearing impairment.…”
Section: Methodsmentioning
confidence: 99%